A preliminary study on the restoration project of St. Vincent de Ferrer Church of Dupax del Sur project implication, and works still left to be done - Argote, Bobby U. (Publication of Engineering & Architecture Researches, 2014)
This research aimed to undergo a preliminary study on the status of the Saint Vincent de Ferrer Church of Dupax del Sur. It exposed the present status in terms of its architectural and structural elements. It also aimed to provide awareness regarding its cultural importance as well as the hazards that might arise. It has been found out that the conservation and restoration of the entity is highly recommended.